Characterization of Acidic Water from the Former Coal Mine of PT Mifa Bersaudara in West Aceh - Kiswanto Kiswanto; Wintah Wintah (Universitas Negeri Semarang, 2025)
Acid coal mine drainage from the coal mining industry contains a number of heavy metal ions and dissolved organic substances. An important step in wastewater treatment so that the waste treatment process runs effectively is to know the characteristics of coal mine acidic water. This study aims to determine the characteristics of coal mine acidic water originating from former coal mine ponds by taking samples from a holding pond located in West Aceh. The method used in this research consists of field work and laboratory work. Samples of coal mine acidic water were taken from the former coal mine pond using grab samples. Furthermore, measurements of acid coal mine water parameters were measured including pH, TSS, COD, Color, Fe and Mn conducted at the integrated laboratory of Diponegoro University. Data obtained from the measurement of acid coal mine water parameters were analyzed descriptively. The measurement results include pH, TSS, COD, Color, Fe and Mn ions contained in coal mine acid water are also compared with the quality standards of liquid waste.The results showed that coal mine acid water in the former coal mine pond contained pH, TSS, COD, Color, Fe ions, and Mn with an average value of (5.5); (260mg/l); (162.82mg/l); (57mg/l); (4.7mg/l); (0.2mg/l). All parameters of coal mine acid water measurement analysis results are still above the quality standards of coal mining based on the Decree of the Minister of Environment No.113 of 2003 concerning Quality Standards for Coal Mining Liquid Waste.